Financial market reaction to patent lawsuits against integrated circuit design companies - Su-Chen Yu; Kuang-Hsun Shih (Journal of Risk and Financial Management, 2021)
With the rapid advancement in technology, Taiwan's integrated circuit (IC) design companies have made a mark in the international semiconductor industry but are unable to independently develop the key core technologies they need. Therefore, strategic alliances, competition and cooperation have become a means for enterprises to quickly obtain patents and capture the market. However, listed companies upstream and downstream of Taiwan's supply chain have been facing patent infringement lawsuits in recent years. This research mainly aims to provide investors with investment strategies when companies face patent litigation, analyze the abnormal returns on the underlying stocks through the event research method, and use the cross-sectional multiple regression model to explore the changes in different factors based on the results. The empirical results show that positive abnormal returns are generated before and after a company faces patent litigation and the cumulative abnormal rewards are all positive and significant after the incident, which indicates that the company may still have an opportunity to make a profit when facing patent litigation, which can be used as a reference for investors.
Keywords: 330; market reaction; IC design; patent defendants; patent lawsuits; patent plaintiffs